Rhetoric and Galatians: assessing an approach to Paul's epistle - Kern, Philip H. (Society for New Testament Studies monograph series, 1998)
This monograph challenges the accepted notion that Galatians is either a sample of classical rhetoric or should be interpreted in light of Graeco-Roman rhetorical handbooks. It demonstrates that the handbooks of Aristotle, Cicero, et al. discuss a form of oratory which was limited with respect to subject, venue and style of communication, and that Galatians falls outside such boundaries. The inapplicability of ancient canons of rhetoric is reinforced by a detailed comparison of Galatians with the handbooks, a survey of patristic attitudes towards Paul's communicative technique, and interaction with twentieth-century discussions of the nature of New Testament Greek. Dr Kern concludes that rhetorical handbooks were never a tool of literary criticism and that they cannot assist the search for a distinctly Pauline rhetoric. Thus this study has implications not only for Galatians, but also for other New Testament epistles.